2004
DOI: 10.1037/0012-1649.40.5.776
|View full text |Cite
|
Sign up to set email alerts
|

The Emotional Integration of Childhood Experience: Physiological, Facial Expressive, and Self-Reported Emotional Response During the Adult Attachment Interview.

Abstract: Attachment researchers claim that individual differences in how adults talk about their early memories reflect qualitatively distinct organizations of emotion regarding childhood experiences with caregivers. Testing this assumption, the present study examined the relationship between attachment dimensions and physiological, facial expressive, as well as self-reported emotional responses during the Adult Attachment Interview (AAI). Consistent with theoretical predictions, more prototypically secure adults behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
189
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(206 citation statements)
references
References 52 publications
(92 reference statements)
15
189
2
Order By: Relevance
“…In prior research, people have been found to smile when frustrated, perhaps as an emotion regulation strategy to reduce frustration (Hoque & Picard, 2011). Facial expressions that are incongruent with the emotional situation have also been considered as reflecting individuals' confusion and emotional dysregulation or the attempt to block the experience and expression of negative emotions (Roisman et al, 2004;Sonnby-Borgström & Jönsson, 2004). During the performance of the neutral cognitive task, individuals experienced a decreased intensity of negative and positive emotions, possibly because concentration is needed to fulfil the task and the task does not make an appeal to specific emotions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In prior research, people have been found to smile when frustrated, perhaps as an emotion regulation strategy to reduce frustration (Hoque & Picard, 2011). Facial expressions that are incongruent with the emotional situation have also been considered as reflecting individuals' confusion and emotional dysregulation or the attempt to block the experience and expression of negative emotions (Roisman et al, 2004;Sonnby-Borgström & Jönsson, 2004). During the performance of the neutral cognitive task, individuals experienced a decreased intensity of negative and positive emotions, possibly because concentration is needed to fulfil the task and the task does not make an appeal to specific emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Diamond and Hicks (2005) showed that attachment anxiety was positively associated with self-reported distress and anger during and after anger-inducing tasks, also expressed by their vagal tone. Studies further report that anxiously and avoidantly attached individuals' facial expressions were incongruent with the emotional situation, which might reflect anxiously attached individuals' confusion and emotional dysregulation and avoidantly attached individuals' attempts to block negative emotions (Roisman, Tsai, & Chiang, 2004;Sonnby-Borgström & Jönsson, 2004). …”
mentioning
confidence: 99%
“…Another important application of automated systems for human affect recognition is in affectrelated research (e.g., in psychology, psychiatry, behavior science, and neuroscience), where such systems can eliminate the tedious manual task of processing data. Research areas like social and emotional development studies [1], mother-infant interaction [2], and psychiatric disorders [3] would be substantially benefited. Automatic detection of fatigue, depression, and anxiety could also form an important step towards personal wellness and assistive technologies [4].…”
mentioning
confidence: 99%
“…Facial Action Unit System (FACS) [13]), more and more reports of emotion analysis have been conducted in psychology, psychiatry, education, anthropology, neurophysiology [14][15] [16]. The emotion-related research includes attachment [17], mother-infant interaction [18], tutoring [19], and psychiatric disorders [20]. All of the above research requires measurement of emotion expressions.…”
Section: Introductionmentioning
confidence: 99%